Generation of multi-wavelength erbium-doped fiber laser by using MoSe2 thin film as nonlinear medium and stabilizer - Tiu, Zian Cheak; Ahmad, Harith; Zarei, A.; Harun, Sulaiman Wadi (Optical Society of America, 2016)
We experimentally demonstrate the application of MoSe2 thin film as a nonlinear medium and stabilizer to generate a multi-wavelength erbium-doped fiber laser. The cooperation of a photonic crystal fiber and a polarization- dependent isolator induces unstable multi-wavelength oscillations based on the nonlinear polarization rotation effect. A MoSe2 thin film is further incorporated into the cavity to achieve a stable multi-wavelength. The laser generates 7 lasings with a constant spacing of 0.47 nm at a pump power of 250 mW. The multi-wavelength erbium-doped fiber laser is stable with power fluctuations of less than 5 dB over 30 min.